Repurposing End-of-Life Coal Mines with Business Models Based on Renewable Energy and Circular Economy Technologies - Alicja Krzemień; Aleksander Frejowski; Gregorio Fidalgo Valverde; Pedro Riesgo Fernández; Silverio Garcia-Cortes (Energies, 2023)
This paper presents a methodology to select the most exciting business models based on renewable energy and circular economy technologies within end-of-life coal mines to help develop a renewable-based energy sector, promote sustainable local economic growth, and maximise the number of green and quality jobs. To achieve this goal, first, a structural analysis was developed to select the technical variables that better identify this complex system. Second, a morphological analysis allowed the construction of the scenario space. Third, a multicriteria assessment was developed to achieve this goal, based on the previously assessed relevant scenarios, considering the European Green Deal policies, technical variables that characterise end-of-life coal mine environments, technology readiness level, the European taxonomy, synergistic potentials, contributions to the circular economy, and sector coupling. Finally, result indicators were selected to analyse the alternative options derived from the justification approach, considering the targets set by the European Green Deal and related taxonomy and the regional policy indicators for the Just Transition Fund. The results show that eco-industrial parks with virtual power plants represent the most appropriate business model choice, according to the scoring given to the different aspects. They may be complemented by a hydrogen production plant, provided that specific economic subventions are obtained to achieve balanced financial results.